2013
DOI: 10.1074/mcp.m113.028241
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Post-translational Responses of Aquaporins to Abiotic and Nutritional Stimuli in Arabidopsis Roots

Abstract: In plants, aquaporins play a crucial role in regulating root water transport in response to environmental and physiological cues. Controls achieved at the post-translational level are thought to be of critical importance for regulating aquaporin function. To investigate the general molecular mechanisms involved, we performed, using the model species Arabidopsis, a comprehensive proteomic analysis of root aquaporins in a large set of physiological contexts. We identified nine physiological treatments that modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 57 publications
2
55
0
Order By: Relevance
“…S4A, S4B). Three phosphorylation sites have been described in PIP2;1, at Ser 121 , Ser 280 , and Ser 283 (1,4,8). The P f of oocytes expressing a PIP2;1 form with Ser-to-Ala mutations at positions 280 and 283 (Ser 280 Ala-Ser 283 Ala) was almost similar to P f of oocytes expressing wild-type PIP2;1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…S4A, S4B). Three phosphorylation sites have been described in PIP2;1, at Ser 121 , Ser 280 , and Ser 283 (1,4,8). The P f of oocytes expressing a PIP2;1 form with Ser-to-Ala mutations at positions 280 and 283 (Ser 280 Ala-Ser 283 Ala) was almost similar to P f of oocytes expressing wild-type PIP2;1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Protein Digestion-In-solution reductions/alkylations were performed simultaneously with detergent removing by the filter-aided sample preparation protocol (1,36). These steps were followed by a endolysin-C (Sequencing Grade Modified, Promega, Madison, WI) digestion 3 h at 37°C followed by a trypsin (Sequencing Grade Modified, Promega) digestion overnight at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, a study of aquaporins (plasma membrane intrinsic proteins [PIPs]) in Arabidopsis roots showed increased deamidation (by MS/MS analysis and spectral counting) in response to (a)biotic stress conditions. Moreover deamidation levels of PIP2 appeared coupled to its phosphorylation status, suggesting cross talk between these PTMs (di Pietro et al, 2013). It was suggested that deamidation could be involved in regulating aquaporin activity.…”
Section: Deamidationmentioning
confidence: 99%